2011
DOI: 10.1073/pnas.1116327108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic modeling of the effects of myoferlin on tumor cell invasion

Abstract: Myoferlin (MYOF) is a member of the evolutionarily conserved ferlin family of proteins, noted for their role in a variety of membrane processes, including endocytosis, repair, and vesicular transport. Notably, ferlins are implicated in Caenorhabditis elegans sperm motility (Fer-1), mammalian skeletal muscle development and repair (MYOF and dysferlin), and presynaptic transmission in the auditory system (otoferlin). In this paper, we demonstrate that MYOF plays a previously unrecognized role in cancer cell inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 39 publications
7
83
1
Order By: Relevance
“…Interestingly, Li and colleagues (14) and Eisenberg and colleagues (13) both showed that short hairpin RNA (shRNA)-mediated myoferlin depletion impairs MDA-MB231 cells' invasion; however, it has no effect on cell migration or proliferation. Our invasion and proliferation data are in agreement with the literature (13,14). However, opposite to the previous findings (13,14), we show that myoferlin silencing exhibits a strong inhibitory effect on the ability of MDA-MB231 cells to migrate.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…Interestingly, Li and colleagues (14) and Eisenberg and colleagues (13) both showed that short hairpin RNA (shRNA)-mediated myoferlin depletion impairs MDA-MB231 cells' invasion; however, it has no effect on cell migration or proliferation. Our invasion and proliferation data are in agreement with the literature (13,14). However, opposite to the previous findings (13,14), we show that myoferlin silencing exhibits a strong inhibitory effect on the ability of MDA-MB231 cells to migrate.…”
Section: Discussionsupporting
confidence: 38%
“…In normal myoblasts, Demonbreun and colleagues showed that myoferlin deficiency leads to a defect in insulin growth factor-like receptor (IGFR1) trafficking as well as to decreased IGFR1 signaling (12). Although increasing number of studies continue to further our understanding of myoferlin function in normal cells, to date, only little (13)(14)(15) is known concerning its role in tumor cells. Three previous studies have reported the overexpression of myoferlin at the mRNA level in lung (16) and breast cancer (17) as well as at the protein level in pancreas cancer (18).…”
Section: Introductionmentioning
confidence: 99%
“…The impedance data, reported as cell index and proportional to the area of the bottom electrodes covered by migrated/invasive cells, were collected every 15 min. The percentage of invasion was calculated as the ratio between the invasive cells and the migrated cells (8).…”
Section: Flow Cytometry Nthy Cells Infected With Empty Vector Vectomentioning
confidence: 99%
“…Recently, myoferlin was found to be important for breast cancer invasion. [13][14][15] Our laboratory showed that myoferlin, is a key regulator of EGFR activity in human breast cancer cells. 16 Interestingly, it was reported, in a Kaplan-Meier survival curve, that patients with myoferlin-positive PDAC had a significant lower overall survival than those with a myoferlinnegative tumor.…”
mentioning
confidence: 99%